Limnology - Some New Aspects of Inland Water Ecology 2019
DOI: 10.5772/intechopen.81747
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Optimum Water Quality Indices in Successful Frog Culture Practices

Abstract: The optimum quality of water indices is extremely important for successful frog culture. Frogs excrete their excreta and skin debris in water. Therefore, it is necessary to regularly renew the water and clean the tanks and bays of rearing systems. Such care is necessary for the prevention and prophylaxis of diseases, which may cause severe mortalities. Bullfrogs need water of good physical and chemical quality, and thus, water quality indices must be measured before starting a breeding and rearing program. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The beds had become spawning grounds of frogs. Factors contributing to increased ammonia production included the presence of tadpoles in the holding tank and the beds becoming spawning grounds for frogs [11]. Frog eggs and tadpoles may potentially raise ammonia concentrations at point 6.…”
Section: Removal Performance According To Ges Parametersmentioning
confidence: 99%
“…The beds had become spawning grounds of frogs. Factors contributing to increased ammonia production included the presence of tadpoles in the holding tank and the beds becoming spawning grounds for frogs [11]. Frog eggs and tadpoles may potentially raise ammonia concentrations at point 6.…”
Section: Removal Performance According To Ges Parametersmentioning
confidence: 99%
“…Water quality optimization, based on rigorous scientific parameters, ensures the well-being of these aquatic companions. Interestingly, studies have shown that maintaining specific water parameters, such as pH levels and temperature, significantly influences ornamental fish's colouration and overall health [7]. Habitat replication, an essential aspect of environmental management, not only enhances the visual appeal of aquariums but also contributes to the overall physiological well-being of the fish [8].…”
Section: Introductionmentioning
confidence: 99%